2000
DOI: 10.1182/blood.v96.3.785
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival and tissue trafficking following adoptive transfer of CD4ζ gene-modified autologous CD4+ and CD8+ T cells in human immunodeficiency virus–infected subjects

Abstract: We have genetically engineered CD4+ and CD8+ T cells with human immunodeficiency virus (HIV) specificity by inserting a gene, CD4ζ, containing the extracellular domain of human CD4 (which binds HIV env) linked to the zeta (ζ) chain of the T-cell receptor (which mediates T-cell activation). Twenty-four HIV-positive subjects received a single infusion of 2 to 3 × 1010 autologous CD4ζ-modified CD4+and CD8+ T cells administered with (n = 11) or without (n = 13) interleukin-2 (IL-2). Subjects had CD4 counts greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…The CD4f construct has been extensively tested in multiple systems such primary T and NK cells against HIV [36][37][38][39][40]. Some of these trials transduced CD4f into primary T-cells of HIV-infected patients with varying effects [37,39]. Here, we combined the unique advantages of the hESCs/ iPSCs system and the specificity and efficacy of CARs together to genetically modify hESCs/iPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD4f construct has been extensively tested in multiple systems such primary T and NK cells against HIV [36][37][38][39][40]. Some of these trials transduced CD4f into primary T-cells of HIV-infected patients with varying effects [37,39]. Here, we combined the unique advantages of the hESCs/ iPSCs system and the specificity and efficacy of CARs together to genetically modify hESCs/iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…As the CD4 protein is an absolute requirement for HIV entry, it is plausible to use this as an effective "antigen recognition" domain independent of human leukocyte antigen restriction. Several groups pioneered this approach to both basic research and clinical trials [36][37][38][39][40]; however, this had varying efficacy in vivo when transduced into patients autologous T-cells. Here, we modified both hESCs and iPSCs with a CD4f construct to generate NK cells that express the specific HIV CD4f chimeric receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of systemic IL2 has been reported to enhance the persistence of adoptively transferred human CD8 + T cells (Yee et al, 2002). However, others have found that using autologous human CD4 + T and CD8 + T cells in combination eliminates the benefit of concomitant IL2 therapy (Mitsuyasu et al, 2000). Recent studies also seem to indicate that IL2 might actually reduce memory T cells and increase the number of T regs (Zhang et al, 2005).…”
Section: Support and Control Of Car T Cellsmentioning
confidence: 99%
“…One such promising supportive approach was pioneered by the laboratory of Carl June whereby CD4 + T cells from HIV-infected patients were shown to expand vigorously with a concomitant elimination of HIV when cultured with beads coated with anti-CD3 and anti-CD28 monoclonal antibodies (mAb) [12,31,45]. Such an approach and variants thereof have allowed for the readministration of long lived autologous CD4 + T cells to patients [17,38]. Furthermore, the pilot administration of autologous anti-CD3/28 expanded CD4 T cells transduced with an antisense vector for HIV was shown to markedly decrease viral load set points in patients in which HAART was discontinued following adoptive transfer [32].…”
Section: Introductionmentioning
confidence: 99%